La Visitation: Inequality and the Social Fabric of Marseille. Issue 1 (September 2017) - Kornblum, William
Unlike many other major metropolitan centers in France, Marseille has not suffered high rates of collective violence and rioting in its public housing estates ( cités ). Yet it is also true that the cités of Marseille are as feared and stigmatized as any in France. This article explores research on the city's housing estates and presents original ethnographic work that helps to explain Marseille's exceptionalism. I find that local efforts at community education by active residents of La Visitation, a typical mid-sized Marseille cité, enhance social cohesion and neighborhood pride, despite persistent problems of underemployment among its young residents. I also describe a successful effort to use a produced video (an application of visual sociology) to draw attention to and support for residents' local initiatives.